Design and Analysis of a Solar-Wind Hybrid Energy Generation System (American Journal of Energy and Natural Resources, 2025)
This paper explores how the increasing demand for renewable energy sources has resulted in the development of innovative technologies to harness solar and wind power. The paper evaluates the potential of solar wind hybrid power generation as a solution to address energy reliability, cost, and environmental sustainability challenges. The paper presents a system that generates electricity using wind and solar power, wherein an external high-speed fan rotates the rotor of a dynamo, producing magnetic flux that creates a DC voltage, and a solar panel absorbs photons of light, creating another DC voltage by freeing electrons. Both outputs are connected to a charge controller, a battery for energy storage, and a load, a motor with a propeller and an LED light. Two diodes ensure that the currents from the wind turbine and solar panel do not oppose each other. The paper also discusses various aspects such as pre-feasibility analysis, optimal sizing, modeling, control, and reliability issues related to the system.